PENGARUH RIWAYAT KELAHIRAN PREMATUR DENGAN KEJADIAN STUNTING DI KABUPATEN BANJARNEGARA - Rusfita Retna; Reni Sumanti (Jurnal Ilmiah Medsains, 2024)
One of the most common causes of stunting is chronic malnutrition, which can be caused by fetal conditions, premature birth or stunted growth. Toddlers who are born prematurely have an increased risk of stunting in the first two years of life. Premature is defined as birth that occurs before 37 weeks of gestation. Babies born prematurely often experience growth and development problems because their body organs and digestive system are not yet mature. Indonesia is a country with a high rate of premature births ranging from 10-11%. So far, premature babies require different treatment than non-premature babies. Premature babies are considered to have a greater risk of developing diseases including stunting. Objective of the study was to determine the effect of a history of premature birth on the incidence of stunting in Banjarnegara Regency. This research is quantitative research carried out using an analytical survey method with a case control approach. The research location is in the stunting locus area of ​​Banjarnegara Regency in 2023. The research results show that there is a significant relationship between premature birth and the incidence of stunting in children under five years of age (toddlers) in Banjarnegara Regency. Children born prematurely have a 4,189 times greater risk of experiencing stunting compared to children who are expected to be born. There is a significant influence between the history of premature births on the incidence of stunting in Banjarnegara Regency